Probability of occurrence of health and safety risks on scaffolding caused by noise exposure - Jabłoński, Marek; Szer, Iwona; Szer, Jacek (Journal of Civil Engineering and Management, 2018)
The paper presents the results of measurements for one hundred and ten scaffolds located in five cities in different parts of Poland. Measurements were made between April of 2016 and October of 2017. The environmental tests performed on scaffoldings were focused mainly on the sound level. The parameters on which we base our analysis are the value of C-weighted peak sound levels and daily noise exposure level. The noise that affects construction workers on scaffolding may influence the behaviour of workers and increase the risk of accidents. And at the same time, noise exposure laws facilitate identification of high noise-emitting activities and provide effective preventive measures that reduce noise pollution and improve work environments. The analyses carried out confirmed the qualitatively expected dependencies, and allowed us to quantify the impact of noise to which scaffolding workers are exposed. In summary, noise measurements on scaffoldings can be a valuable aid in improving working conditions. The analysis of research results allows understanding hazards related to noise in an accessible way. They provide the opportunity to modify the professional environment so that it is more employee-friendly and does not expose them to problems occurring in a noisy work environment.